ANALISA PENGARUH INTENSITAS SUMBER CAHAYA PENGINDUKSI FLUORESENSI TERHADAP INTENSITAS FLUORESENSI KLOROFIL PADA DAUN BAYAM MENGGUNAKAN METODE FLUORESCENCE IMAGING - Minarni '; Iswanti Sihaloho (Universitas Riau, 2015)
Chlorophyll fluorescnce imaging and spectroscopy has been developed intensively during last decade to detect early symptoms of plant diseases and effects of environtmental stresses on plants. An economical, portable, and remote sensing system is needed for those purposes. In this research, a fluorescence imaging system was built using a LED with 465 nm wavelength, some neutral density filters and a 3 Mega Pixel CMOS camera. The intensities of LED light were varied using 5 different optical densities of the neutral density filters which were represented by their optical power after filtered 5,0 mW; 3,3 mW; 2,0 mW; 1,5 mW; and 0,7 mW respectively. This system was used to investigate the relation between the intensity of LEDs as a fluorescence inducer and the fluorescence intensity of spinach leaves grown under two variations of sunlight intensity. The variations were about 90% using plastic cover and 40% using plastic plus paranet cover. The spinach plant was Amaranthus tricolar varitas. The differences between chlorophyll fluorescence intensity of the spinach leaves for both treatment were also investigated. The fluorescence intensities were found from RGB plot using ImageJ software. The reseach results showed that intensity of LED light influenced the fluorescence intensity resulted on the spinach leaves. The higher the intensity of LED, the higher the fluorescence intensity. The spinach leaves grown without paranet provided higher fluorescence intensity however, the difference between both treatments was seen higher when LED intensity was the lowest which was about 41,6% difference.